Measurement and research methods in international marketing - Sarstedt, Marko; Schwaiger, Manfred, 1963-; Taylor, Charles R., 1961- (Bingley, U.K. : Emerald, 2011)
Publishing cross-national research is often a difficult endeavour as ensuring equivalence of method and measures can be challenging. Even though the importance of sound data and valid measures has long been an acknowledged, it is often problematic to follow required quality standards in concrete research situations. Against this background, this volume addresses issues pertaining measurement and research methodology in an international marketing context. Written by a group of internationally renowned scholars, the papers address a broad range of subjects including response-bias in cross-cultural research, problems with cultural distance measures, and construct specification. Others focus on the development and application of novel research methods, for example in the context of marketing efficiency measurement or international market segmentation. Collectively, the papers in this volume substantially further marketing knowledge and provide fruitful avenues for future research. As such, this volume is an invaluable asset to researchers, students and practitioners in this particular field.
Introduction : measurement and research methods in international marketing / Marko Sarstedt, Manfred Schwaiger, Charles R. Taylor -- Using formative measures in international marketing models : a cautionary tale using consumer animosity as an example / Adamantios Diamantopoulos, Petra Riefler -- Difference scores, analysis levels, and the (mis)interpretation of cultural distance / George R. Franke, John S. Hill, Jase Ramsey, R. Glenn Richey -- The role of response formats on extreme response style : a case of Likert-type vs. semantic differential scales / Joseph F. Rocereto, Marina Puzakova, Rolph E. Anderson, Hyokjin Kwak -- A multicountry advertising research framework : lessons learned from testing global consumer culture positioning / Shintaro Okazaki, Barbara Mueller, Sandra Diehl -- Stochastic frontier estimation in international marketing research : exploring untapped opportunities / Matthew E. Sarkees, Ryan Luchs -- Marketing accountability : applying data envelopment analysis to assess the impact of advertising efficiency on shareholder value / Sascha Raithel, Sebastian Scharf, Charles R. Taylor, Manfred Schwaiger, Lorenz Zimmermann -- The state of methodological practice in international marketing research / Charles R. Taylor, C. Luke Bowen, Hae-Kyong Bang -- Assessing heterogeneity in customer satisfaction studies : across industry similarities and within industry differences / Edward E. Rigdon, Christian M. Ringle, Marko Sarstedt, Siegfried P. Gudergan -- Multigroup analysis in partial least squares (PLS) path modeling : alternative methods and empirical results / Marko Sarstedt, Jèorg Henseler, Christian M. Ringle -- Introduction to section II : regular articles / Shaoming Zou -- Consumer complicity across emerging markets / Peggy E. Chaudhry, Ronald Paul Hill, Stephen A. Stumpf, Goksel Yalcinkaya.
Keywords: Export marketing; Marketing research